Musical biography of Sultan Sulaiman (Head of Serdang Sultanate V, 1880-1946) / Ifwanul Hakim - Ifwanul , Hakim (2019)
This work presents an academic study of the musical biography of Sultan Sulaiman, the fifth head of Serdang Sultanate, North Sumatera, Indonesia, in period 1880-1946. The discussion will lead to personal and cultural view including discussing the musical life of the Sultan and the impact of his musical thinking and activity for the cultural situation in the Sultanate. By personal, it will examine about the Sultan’s music spirit, thinking, and activity. Personally, as a violinist, it aims to find out how he learn, where the influence he got from, what type at repertoire, and the reason why he got interest into music. Moreover, it is interesting to analyse his own music composition that will be analise to framing his musical idea. While by socially will be concern on anything he did for music development in Serdang Sultanate during his commander and the impact after his period. In addition, this study will be presents in brief the correlation between Sultan’s music activity and the political situation at that time. Researcher provide some introduction throughout the reign of Sultan Sulaiman where Serdang live under Dutch colonialism for the longest time. By doing analysis for Sultan Sulaiman’s musical work, concludes that the main idea of his music is telling about his state and the ideas of nationalism. Then found that Sultan Sulaiman is the root of arts development in the Serdang Sultanate. This is evidenced by the many art activities he conserve and develop such as Nobat Diraja, Mak Yong, Brass Band, and Serampang Dua Belas dance. The activities he did on the past give many impact for art development in Serdang in nowadays. The spirit of art continious by his offsprings. It also stated that the art’s idea of Sultan Sulaiman is a part of political strategy. This research provide guidelines for future researcher who enthusiasm to doing research in musical biography to find more complete data in the form of text, images, as well as audio to get the better results. This research is divided into five chapters. Chapter 1 contains an introduction of the research, where the research background, research objective and research question is presented. Chapter 2 presents the literature review, which covers the literatures of the life background of Sultan Sulaiman, as well as music analysis theories in western and melayu approach that could be applied into this research. The research methodologies are explained thoroughly in chapter 3. Chapter 4 displays the discussion of the musical life of Sultan Sulaiman, as well as the analysis the musical work (composition) of Sultan Sulaiman. A summary and findings are highlighted in chapter 5, as well as suggestions for future researches.